THE INJURY RESISTANT ABILITY OF MELANOPSIN-EXPRESSING INTRINSICALLY PHOTOSENSITIVE RETINAL GANGLION CELLS - Cui, Q. (Neuroscience, 2014)
Neurons in the mammalian retina expressing the photopigment melanopsin have been identified as a class of intrinsically photosensitive retinal ganglion cells (ipRGCs). This discovery more than a decade ago has opened up an exciting new field of retinal research, and following the initial identification of photosensitive ganglion cells, several subtypes have been described. A number of studies have shown that ipRGCs subserve photoentrainment of circadian rhythms. They also influence other non-image forming functions of the visual system, such as the pupillary light reflex, sleep, cognition, mood, light aversion and development of the retina. These novel photosensitive neurons also influence form vision by contributing to contrast detection. Furthermore, studies have shown that ipRGCs are more injury-resistant following optic nerve injury, in animal models of glaucoma, and in patients with mitochondrial optic neuropathies, i.e., Leber’s hereditary optic neuropathy and dominant optic atrophy. There is also an indication that these cells may be resistant to glutamate-induced excitotoxicity. Herein we provide an overview of ipRGCs and discuss the injury-resistant character of these neurons under certain pathological and experimental conditions.